Adverse Effect of Infrastructure Development in the Habitat and Distribution of Chinese Pangolin in Chandragiri Hill, Kathmandu (Journal of Wildlife and Conservation, 2023)
The Chinese Pangolin (Manis pentadactyla) is a nocturnal and elusive animal that relies on a specialized diet consisting of ants and termites. It enjoys national and international protection, but the current conservation measures remain insufficiently developed. The escalating threats of habitat loss, habitat degradation, and habitat fragmentation have pushed the pangolin to a highly endangered state in Nepal. The study conducted on Chandragiri Hill aimed to investigate the conservation status and distribution patterns of the Chinese Pangolin, as well as its habitat preferences and the potential impact of infrastructure development on both the pangolin and its habitat. The data collection process involved direct field observations, where various indicators of pangolin presence, such as burrows, were carefully documented. These observations were then utilized to generate a distribution map of pangolin burrows, employing ArcGIS-10.3 software. Out of a total of 43 burrows observed, 37 were found to be inactive while the remaining 6 were active. The study revealed that the population of burrows was highest within the elevation range of 1600m to 1700m. Furthermore, burrow density was found to be significantly higher at a distance of 100m horizontally from the cable car pathway compared to a distance of 20m horizontally from the same pathway.